Emergent bacteria in cystic fibrosis: in vitro biofilm formation and resilience under variable oxygen conditions - Lopes, Susana Patrícia (2014)
Concurrently to conventional bacterial pathogens, unusual microbes are emerging from cystic fibrosis (CF) airways. Nonetheless, little is known about the contribution of these newly microbes for the resilience of CF-associated biofilms, particularly under variable oxygen concentrations that are known to occur in vivo in the mucus of CF patients. Two CF-emergent bacterial species, Inquilinus limosus and Dolosigranulum pigrum, and the major pathogen Pseudomonas aeruginosa were studied in terms of biofilm development and antibiotic susceptibilities under in vitro atmospheres with different oxygen availabilities. All species were able to develop in vitro biofilms under different oxygen-available environments, with D. pigrum accumulating high amounts of biomass and respiratory activities. When established, biofilms were of difficult eradication, with antibiotics loosing their effectiveness in comparison with the corresponding planktonic populations. Surprisingly, biofilms of each emergent organism displayed multi-drug resistance under aerobic environments, enduring even in low-oxygen atmospheres. This study suggests a potential prospect on the impact of non-conventional organisms I. limosus and D. pigrum on CF lung infections, demonstrating capacity to adapt to biofilm mode of life under restricted-oxygen atmospheres resembling CF airways, which may ultimately endanger the efficacy of currently-used antibiotic regimens.